Peran P4S Amulat Terhadap Perubahan Perilaku Petani Pada Usahatani Komoditas Kedelai di Kalurahan Bleberan, Gunungkidul - Widyarini, Darana; Euriga, Epsi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Amulat Agricultural and Rural Self-Help Training Center (P4S) is a farmer institution based on self-help located in Bleberan Village, Kapanewon Playen, Gunungkidul Regency, with soybean (Glycine max L.Mer) as the leading commodity. However, the majority of farmers pay less attention to their farms, due to various limitations. This study aims to determine how the role of P4S Amulat as a farmer institution based on self-help training on farmer behavior on soybean commodity farming. This research uses a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The data analysis technique used is narrative data analysis, with descriptive writing method. The results showed that P4S Amulat has a role as a motivator, provider of facilities and infrastructure, consultant, business network, training and apprenticeship. The role of P4S Amulat is influential in changing the behavior of farmers in Bleberan Village. Changes in farmer behavior can be seen from the aspects of knowledge, attitudes, and skills possessed by farmers. Changes in farmer behavior have had a positive impact on soybean farming activities, with increased community welfare in Bleberan Village.